Meaningful Management: A Millennial Perspective of Woolworths’ Food Waste Management Practices - Mohamed, Nieyyaaz (The IIE, 2022)
Despite the evolution of our abilities to preserve food to ensure the sustenance of humanity, an estimated one-third of the global food production is lost or wasted along the food supply chain each year. This highlights a contradiction between global food waste and food scarcity, identifying the increasing problem of inefficiency in the food production system. South Africans have suffered at the hands of this scarcity, with nearly 40% of citizens experiencing food insecurity. Retailers and their consumers occupy essential positions within the food supply chain respectively, and their relationship has been studied extensively in the context of food waste, management and prevention. A gap in the research, however, exists in relation to customer perceptions of retailers’ commitment to food waste management and the implementation of practices mitigating food waste along the retail food supply chain. Also requiring further study are customer behaviours - both shopping and domestic - because of being influenced by retailers’ food waste management policies and protocols. A Positivist, correlational research survey was conducted among Woolworths’ Millennial customers to identify potential correlations between the brand’s food waste management practices and the influence of these on customer perceptions and behaviours. Based on the survey results, it was discovered that respondents already support the Woolworths brand and care about food waste management but were largely unaware that Woolworths had these policies and practices in place. Once made aware, most Woolworths’ Millennial consumers surveyed perceived the brand more positively in light of these policies. Though a certain segment of respondents indicated a willingness to support the brand more regularly as a result, others remained neutral or declined to support Woolworths more often, and the question regarding domestic behaviours showed that Woolworths’ food waste management practices had failed to influence consumers to adopt similar practices at home.
Keywords: Food insecurity; Retail; Millennials; Consumer behavior; Food supply chain